If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 10 = 69 Reorder the terms: 10 + 13x = 69 Solving 10 + 13x = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 13x = 69 + -10 Combine like terms: 10 + -10 = 0 0 + 13x = 69 + -10 13x = 69 + -10 Combine like terms: 69 + -10 = 59 13x = 59 Divide each side by '13'. x = 4.538461538 Simplifying x = 4.538461538
| 5u-8v+9(2u-3v)-4(2v-5u)= | | 3x^4+5x^3-x^2-5x-2=0 | | 130-25t=15 | | (4x-3)2+7=39 | | x*3+x*2-12=0 | | 5x^2+20x-30=15 | | 23x+6-27x=2-8 | | 5c+2=5c+4 | | z=10-2x^2 | | f(-5)=(x^2)-5x+7 | | Ax+3=6x+b | | 3x^2+2x+10=900 | | 4x-8=12(4+3x) | | -19(5c-8)-12c= | | (4x-12)(x+7)=0 | | p=140-0.5x | | -6=2x-1x | | 6x^2+22x-18=0 | | y=-a-x | | Ln(x)=24 | | 6x^2+22-18=0 | | 6a=6a+12 | | x(x-4)(x+14)=0 | | ax+1=bx-y | | P=80x-.4x^2-200 | | .8x-4=2x-3 | | 21x-5x=32 | | 9x+1=6x+6 | | 32-6x=14-9x | | z-i=2z-1 | | x+7-6x=-23 | | 4x+14=23 |